Taxonomic additions of the Brazilian fauna of Prosierola (Hymenoptera, Bethylidae) - Pereira, Leonardo Rezeda; Brito, Chirlei Dias de; Azevedo , Celso Oliveira (EntomoBrasilis, 2023)
Prosierola is characterized by having a pair of conspicuous anteromedial metapostnotal foveae on the metapectal-propodeal disc. Little is known about this genus because it is rarely sampled in collections. Therefore, the main goal of this contribution is to expand the knowledge of intraspecific morphological variations and geographical distribution of its species that occur in Brazil. We sorted material from the main collections and obtained 69 specimens of Prosierola nasalis (Westwood) recorded for the first time from Maranhão, Minas Gerais, Pará, Rio Grande do Norte and Rio Grande do Sul; one of Prosierola obliqua Evans recorded for the first time from Distrito Federal; five of Prosierola rotunda Schiffler & Azevedo recorded for the first time from Pará; and 13 of Prosierola rufescens Evans recorded for the first time from Brazil (Amazonas, Bahia, Espírito Santo, Minas Gerais). The mesoscuto-scutellar foveae placed on the dorsal surface of the mesoscutellum shown to be highly variable in size, distance, and shape at both the intra- and interspecific levels.